Corpora Amylacea of Brain Tissue from Neurodegenerative Diseases Are Stained with Specific Antifungal Antibodies - Pisa, Diana; Alonso, Ruth; Rábano, Alberto; Carrasco, Luis (Frontiers in Neuroscience, 2016)
The origin and potential function of corpora amylacea (CA) remains largely unknown. Low numbers of CA are detected in the aging brain of normal individuals but they are abundant in the central nervous system of patients with neurodegenerative diseases. In the present study, we show that CA from patients diagnosed with Alzheimer’s disease (AD) contain fungal proteins as detected by immunohistochemistry analyses. Accordingly, CA were labeled with different anti-fungal antibodies at the external surface, whereas the central portion composed of calcium salts contain less proteins. Detection of fungal proteins was achieved using a number of antibodies raised against different fungal species, which indicated cross-reactivity between the fungal proteins present in CA and the antibodies employed. Importantly, these antibodies do not immunoreact with cellular proteins. Additionally, CNS samples from patients diagnosed with amyotrophic lateral sclerosis (ALS) and Parkinson’s disease (PD) also contained CA that were immunoreactive with a range of antifungal antibodies. However, CA were less abundant in ALS or PD patients as compared to CNS samples from AD. By contrast, CA from brain tissue of control subjects were almost devoid of fungal immunoreactivity. These observations are consistent with the concept that CA associate with fungal infections and may contribute to the elucidation of the origin of CA.